Emerging Psychobiotics: Direct and Indirect Impacts on Mental Health (Development Engineering Conferences Center Articles Database, 2025)
Anxiety, stress, and depression constitute a significant global health burden, with projections suggesting a continued rise in prevalence and societal impact in the coming decade. While conventional pharmacological and psychological interventions offer relief, their limitations, including side effects and treatment resistance, underscore of novel therapeutic avenues. This comprehensive review aims to examine the direct and indirect mechanisms through which psychobiotics—live microorganisms, prebiotics, or synbiotics that confer mental health benefits—exert their influence on the brain-gut axis to ameliorate symptoms of anxiety, stress, and depression. We synthesize evidence from preclinical and clinical studies, highlighting the critical role of specific bacterial strains such as *Lactobacillus helveticus R0052*, *Bifidobacterium longum R0175*, *Lactobacillus casei Strain Shirota*, and *Limosilactobacillus fermentum L18* in modulating neurotransmitter production (GABA, serotonin, dopamine), reducing inflammation, and regulating the hypothalamic-pituitary-adrenal (HPA) axis. Furthermore, the review discusses the indirect effects of psychobiotics through enhancement of gut barrier integrity and modulation of the overall gut microbiota composition. While promising, the field faces challenges related to study heterogeneity and the need for personalized approaches. This review concludes that psychobiotics, with their multifaceted actions, hold substantial promise as future interventions, either as monotherapies or adjuncts, in the management of these pervasive neuropsychiatric conditions.